New aspects in the pathogenesis of miscarriage in women with extragenital pathology - I.V. Loskutova; R.G. Bichevska; N.G. Korniiets (Publishing House TRILIST, 2021)
Study objective: to determine the dynamics of type 9 metalloproteinase (MMP-9) and its tissue inhibitor-1 (TIMP-1) in the pathogenesis of early miscarriage in women with chronic diseases of the hepatobiliary system. Materials and methods. The study included 39 women with a history of early pregnancy miscarriage, who were diagnosed with chronic liver diseases as a result of clinical, instrumental and laboratory studies (17 persons with steatosis and 22 persons with non-alcoholic steatohepatitis). The control group consisted of 8 women without somatic pathology and 8 pregnant women at the first trimester of gestation. MMP-9 and TIMP-1 value in the blood serum was determined by the enzyme immunoassay. Results. MMP-9 and TIMP-1 growth in the blood serum of women with a history of miscarriage was established in the pre-gravidar period. The most significant increase in the parameters of the intercellular matrix was found in patients with non-alcoholic steatohepatitis. MMP-9 and TIMP-1 increased in in blood serum in the first trimester in women with liver diseases. MMP-9 increased against the background of a decrease in the TIMP-1 activity in patients with the threat of premature pregnancy termination. Miscarriage was diagnosed in patients with a minimum value of a tissue inhibitor. Conclusions. There is an imbalance between MMP-9 and TIMP-1 in the blood serum in women with early miscarriage and chronic diseases of the hepatobiliary system. MMP-9 and TIMP-1 level in patients with hepatic steatosis is lower than in patients with non-alcoholic steatohepatitis. MMP-9 increased during physiological pregnancy, and the TIMP-1 activity practically did not change, which indicates the role of MMP-9 in the initial stages of placentation. MMP-9 value in women with a burdened premorbid background with a physiological course of pregnancy and threatening early spontaneous miscarriage was significantly different. The highest activity of MMP-9 was in women with the threat of spontaneous miscarriage in the early stages. TIMP-1 in the first trimester in women with chronic liver disease increased in those with a favorable course of pregnancy and decreased in the threat of spontaneous miscarriage. Such changes in MMP-9 and TIMP-1 in patients with miscarriage indicate the accumulation of intercellular matrix and sclerotic changes in the vessels that provide blood to the uterus.